Application and Development of Multi-Hulls - Dubrovsky, Victor A. (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2014)
A brief history of the expanded application of multi-hull ships and boats is shown. The possibilities of catamaran development are proposed. The first line of multi-hull development is the wider use of various types of multi-hulls. The second line of development is a special method of designing, including complex comparison of seaworthiness. The proposed method ensures the elimination of the disadvantages of multi-hulls, and the fullest realization of their advantages. Practical examples of the developments are shown.